TRPC3 channel confers cerebrovascular remodelling during hypertension via transactivation of EGF receptor signalling. (23rd November 2015) - Wang, Mi; Tang, Yong-Bo; Ma, Ming-Ming; Chen, Jing-Hui; Hu, Chang-Ping; Zhao, Shui-Ping; Peng, Dao-Quan; Zhou, Jia-Guo; Guan, Yong-Yuan; Zhang, Zheng
Abstract: Aims: Ionic perturbation in vascular smooth muscle cells contributes to cerebrovascular remodelling in the setting of hypertension, but the role of transient receptor potential (TRP) channel superfamily remains unknown. The present study was conducted to define the contribution of TRP channels to cerebrovascular remodelling. Methods and results: By integrating quantitative PCR, western blotting, patch clamping, and Ca 2+ imaging, we identified TRP channel, subfamily canonical, member 3 (TRPC3) as the channel subtype most considerably elevated in basilar arteries of two-kidney, two-clip stroke-prone hypertensive rats. Importantly, administration of pyrazole 3 (Pyr3), a TRPC3 channel blocker, attenuated cerebrovascular remodelling. During hypertension, epidermal growth factor receptor (EGFR) was transactivated, as evidenced by marked EGFR phosphorylation, increased pro-HB-EGF shedding, and elevated activity of ADAM17 (HB-EGF sheddase). ADAM17 activity was increased owing to enhanced activation rather than elevated expression. Remarkably, Pyr3 treatment suppressed EGFR transactivation in hypertension. In proliferating basilar artery smooth muscle cells or basilar arteries of hypertensive rats, co-immunoprecipitation assay revealed an interaction between TRPC3 and ADAM17 upon Ang II stimulation. Conclusion: Collectively, we demonstrated that enhanced EGFR transactivation, due to increased TRPC3 expression and functional coupling of TRPC3/ADAM17, resulted in cerebrovascular remodelling. Therefore, TRPC3-induced EGFR transactivation may be therapeutically exploited to prevent hypertension-induced cerebrovascular remodelling.